2020
DOI: 10.7759/cureus.10776
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Maladaptive Daydreaming on Grade Point Average (GPA) and the Association Between Maladaptive Daydreaming and Generalized Anxiety Disorder (GAD)

Abstract: This study demonstrates the prevalence of the maladaptive daydreaming (MD) and generalized anxiety disorder (GAD) among Saudi medical students. It also illustrates the association of MD with both GAD and the students' grade point average (GPA). MD was assessed by using the 14-item Maladaptive Daydreaming Scale (MDS), and GAD was assessed by using both the 7-item Generalized Anxiety Disorder (GAD-7) questionnaire and the Penn State Worry Questionnaire (PSWQ). Our data estimate the prevalence of MD among the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…The difference between the two percentages might be explained by many factors; a clear explanation is the wide cultural differences between the Sudanese and the American population; another possible explanation is the presumable lack of sufficient knowledge of the concept and the experience of maladaptive daydreaming among the study population, which is a plausible explanation because 24.1% of the study participants were not familiar with the concept of maladaptive daydreaming. One important finding regarding the experience of normal daydreaming is that there was no significant correlation between daydreaming and gender of medical students at the UofK-MED (P=0.179); the same finding was found in many similar studies [ 5 , 6 , 8 ]…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…The difference between the two percentages might be explained by many factors; a clear explanation is the wide cultural differences between the Sudanese and the American population; another possible explanation is the presumable lack of sufficient knowledge of the concept and the experience of maladaptive daydreaming among the study population, which is a plausible explanation because 24.1% of the study participants were not familiar with the concept of maladaptive daydreaming. One important finding regarding the experience of normal daydreaming is that there was no significant correlation between daydreaming and gender of medical students at the UofK-MED (P=0.179); the same finding was found in many similar studies [ 5 , 6 , 8 ]…”
Section: Discussionsupporting
confidence: 67%
“…Regarding the MDS score, the mean of MDS score among the study population was found to be 33.66, which is still considered less than the 45% cutoff point measurement for MD. As mentioned in the “ Results ” section, 34.3% of total students were found to be MDers; on the other hand, 70% of the of students were found to be MDers in a similar study conducted on Saudi medical students [ 8 ], while in Italy 17% of adult Italian population during the COVID-19 lockdown were identified as MDers [ 11 ]; again, this could be explained by cultural, socioeconomic, and demographic differences between the countries. Additionally, the two abovementioned studies was conducted on 380 students chosen by convenient sampling, whereas this study population was chosen by random sampling.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most frequent comorbid DSM-5 disorders are attention-deficit hyperactivity disorder, anxiety disorders, depressive disorder, obsessive-compulsive or related disorder (Somer et al, 2017a ). Specifically, many MDers with anxiety and depression were more likely to engage in MD as a means to flee from their unpleasant circumstances (Somer, 2002 ; Alenizi et al, 2020 ). Conversely, comorbidity with psychosis was rare.…”
Section: Introductionmentioning
confidence: 99%